Finite element simulations of shear aggregation as a mechanism to form platinum group elements (PGEs) in dyke-like ore bodies - Mbandezi, Mxolisi Louis (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2002)
This research describes a two-dimensional modelling effort of heat and mass transport in simplified intrusive models of sills and their feeder dykes. These simplified models resembled a complex intrusive system such as the Great Dyke of Zimbabwe. This study investigated the impact of variable geometry to transport processes in two ways. First the time evolution of heat and mass transport during cooling was investigated. Then emphasis was placed on the application of convective scavenging as a mechanism that leads to the formation of minerals of economic interest, in particular the Platinum Group Elements (PGEs). The Navier-Stokes equations employed generated regions of high shear within the magma where we expected enhanced collisions between the immiscible sulphide liquid particles and PGEs. These collisions scavenge PGEs from the primary melt, aggregate and concentrate it to form PGEs enrichment in zero shear zones. The PGEs scavenge; concentrate and 'glue' in zero shear zones in the early history of convection because of viscosity and dispersive pressure (Bagnold effect). The effect of increasing the geometry size enhances scavenging, creates bigger zero shear zones with dilute concentrate of PGEs but you get high shear near the roots of the dyke/sill where the concentration will not be dilute. The time evolution calculations show that increasing the size of the magma chamber results in stronger initial convection currents for large magma models than for small ones. However, convection takes, approximately the same time to cease for both models. The research concludes that the time evolution for convective heat transfer is dependent on the viscosity rather than on geometry size. However, conductive heat transfer to the e-folding temperature was almost six times as long for the large model (M4) than the small one (M2). Variable viscosity as a physical property was applied to models 2 and 4 only. Video animations that simulate the cooling process for these models are enclosed in a CD at the back of this thesis. These simulations provide information with regard to the emplacement history and distribution of PGEs ore bodies. This will assist the reserve estimation and the location of economic minerals.
Keywords: Platinum group; Magmas; Shear flow; Geophysics; Terrestrial heat flow